2009
DOI: 10.2355/isijinternational.49.1615
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vanadium Microalloying in Austenite Conditioning and Pearlite Microstructure in Thermomechanically Processed Eutectoid Steels

Abstract: Multipass torsion tests were carried out with two eutectoid steels, one microalloyed with vanadium, using different deformation sequences. The aim of the study was to investigate the potency of vanadium in the retardation of recrystallization for accumulating strain in the austenite. The study showed that at certain deformation conditions well defined non-recrystallization temperatures (T nr ) were observed in the vanadium microalloyed steel. As a consequence, an increase in the austenite grain boundary area p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…4, Table 3, some previous results obtained for the plain C-Mn2 steel 12) in Table 1 and those obtained with steel 11VN in Ref. 13), the following expression was obtained for the f treat term of Eq. (5): ....... (8) where CR is in °C/s and S V in mm…”
Section: Effect Of Process Parameters On Hardnessmentioning
confidence: 57%
See 4 more Smart Citations
“…4, Table 3, some previous results obtained for the plain C-Mn2 steel 12) in Table 1 and those obtained with steel 11VN in Ref. 13), the following expression was obtained for the f treat term of Eq. (5): ....... (8) where CR is in °C/s and S V in mm…”
Section: Effect Of Process Parameters On Hardnessmentioning
confidence: 57%
“…In this figure two additional values obtained for steel 11VN in a previous work were included because they provided data in the range of larger S V values and thus could be helpful to improve the fitting. 13) From the data shown in Fig. 12, it is observed that as S V increases the microstructural D p unit size decreases.…”
Section: Crystallographic Ferrite Unitmentioning
confidence: 96%
See 3 more Smart Citations